PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PADA MATA PELAJARAN IPS TERPADUDENGAN KOMPETENSI DASAR MENDESKRIPSIKAN HUBUNGAN ANTARA KELANGKAANSUMBER DAYA DENGAN KEBUTUHAN MANUSIA YANG TID - Ahmad Hafas Rasyidi (STKIP PGRI SITUBONDO, 2016)
The research was conducted from April 20th until May 30th 2015 with the research object was students of Class VIII-C as many as 28 students. The design of this study is a Hopkins scheme model, with 4 phases, that wew planning, action, observation and reflection. Data collection technique which used in this study were observation, interviews and tests. Data analysis in this study used a qualitative descriptive analysis. The results of this study showed an increase in student’s learning activity and student’s learning outcomes. Student’s learning activities before the action was quite active criteria. From the analysis of student’s learning activity on the first cycle obtained 78.57% and the percentage of daily tests on the first cycle obtained classical mastery 78.57%. This shows that the implementation of Numbered Head Together (NHT) learning model in the first cycle was not successful, and then this study would be continued to the second cycle. Student’s learning activity in the second cycle was in the active category with the percentage of 86.11%, while the analysis of daily tests on the second cycle obtained classical mastery 85.71%. The achievement of students on daily tests showed that Numbered Head Together (NHT) learning model have been successful and have been able to bring students to increase their learning outcomes. It can be concluded that the learning models which used by teachers greatly affect to student’s learning activity learning outcomes. It can be proven in the implementation of Numbered Head Together (NHT) learning model in Integrated Social Science Subject on Class VIII-C State Junior High School 1 Jangkar Situbondo, which has achieved the classical mastery.